A new pathway for naproxen utilisation by Bacillus thuringiensis B1(2015b) and its decomposition in the presence of organic and inorganic contaminants. (1st June 2019) - Górny, Dorota; Guzik, Urszula; Hupert-Kocurek, Katarzyna; Wojcieszyńska, Danuta
Abstract: Bacillus thuringiensis B1 (2015b) is a bacterial strain that is able to degrade naproxen. However, the potential effect of water co-contaminations on the degradation process and its pathway have not yet been evaluated. The results of our study show that in the presence of aromatic compounds, the B1 (2015b) strain utilised naproxen with an efficiency that was similar to what it was with no aromatic co-contaminations. In the presence of methanol, biodegradation of naproxen was inhibited, while the addition of ethanol increased the decomposition of naproxen. Among the metal ions that were tested, only cobalt (II) and cadmium (II) negatively affected the degradation of the drug. An analysis of the intermediates and enzymes that are engaged in degrading naproxen revealed that the key metabolites are O -desmethylnaproxen, which is the product of tetrahydrofolate-dependent O -demethylase activity, and salicylic acid. Salicylic acid can then be hydroxylated to catechol or gentisic acid or can be cleaved to 2-oxo-3, 5-heptadienedioic acid. The high activity level of catechol 1, 2-dioxygenase indicated that the main degradative pathway of naproxen in the B1 (2015b) strain is via catechol cleavage. Highlights: Bacillus thuringiensis B1 (2015b) degrades naproxen by salicylic acid as intermediate. O -demethylase & catechol 1, 2-dioxygenase are the key enzyme of naproxen degradation. Cr(VI) and Cu(II) has not negative effect on naproxen biodegradation. Aromatic compounds do not inhibit or slightly decreases naproxen degradation.